Can Testicular Size Be a Predictive Factor for Successful Sperm Retrieval in Patients with Non Obstructive Azoospermia? - yumusak, Omer; Cinar, Mehmet; Kahyaoglu, Serkan; Tasci, Yasemin; Buyuk, Gul Nihal; Oksuzoglu, Aysegul (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Non-obstructive azoospermia, defined as absence of spermatozoa in the ejaculate caused by impaired spermatogenesis, is the most severe cause of male infertility. It is typically presented as high serum follicle stimulating hormone levels and atrophic testis. The combination of intracytoplasmic sperm injection and Microdissection testicular sperm extraction allows these infertile men the opportunity to have their own children from their own testis. Our aim was to evaluate the outcomes of micro-Testicular sperm extraction in men with atrophic testis. Study Design: The medical records of 80 non-obstructive men with azoospermia who underwent micro-TESE were retrospectively evaluated. We assessed clinical parameters; age, duration of infertility, smoking, chromosomal karyotype, Y chromosome microdeletion, follicle stimulating hormone, luteinizing hormone, total testosterone and testicular volume in relation with Microdissection testicular sperm extraction results. Results: Testicular sperm retrieval rate was 53% in 80 patients. Testicular volume, serum follicle stimulating hormone and total testosterone concentrations showed correlation with the results of sperm retrieval. These three parameters were found to be significant risk factors with testicular sperm extraction negative patients (p<0.001). The odds ratios (95% CI) were 6.39 (1.25–26.58), 1.24 (1.11-1.36), 1.13 (0.99-1.21) respectively. Testicular volume was found to be a discriminative parameter in patients with negative sperm retrieval. The cut-off point was established as 6.75 ml for testicular volume with 88.1% sensitivity, 62.1% specificity. Conclusion: Microdissection testicular sperm extraction is the most effective procedure for patients with non-obstructive azoospermia. Testicular volume, serum follicle stimulating hormone and testosterone levels can be predictive factors for sperm retrieval in men with non-obstructive azoospermia.